Teachers’ Emotional Intelligence and Its Impact on Students’ Academic Achievement in Science Subjects at the Secondary Level - Akhtar, Naeem; Mehmood, Tahir; Batool, Uzma (JSE, 2024)
Emotional intelligence (EI) of teachers has become a buzzword that affects teaching performance and academic achievement of students, especially in cognitively challenging areas like science in secondary school level. This paper will look at the effects of emotional intelligence in teachers on the academic performance of students in science subjects such as biology, chemistry, and physics. EI, which includes self-awareness, self-regulation, motivation, empathy, and social skills, would help teachers to deal with emotions in the classroom, promote positive teacher-student interactions and environmentally friendly learning conditions that are favorable to academic activities. Data was gathered by applying the quantitative research design method to secondary school science teachers and students using the standardized emotional intelligence questionnaires and the academic achievement scores of the students. To establish the strength and nature of the relationship between EI of teachers and performance of students in science subjects, statistical tests such as correlation and regression tests were conducted. The results indicate that there is a strong positive correlation between the emotional intelligence of teachers and the academic performance of students, which implies that teachers that possess greater EI are more efficient in motivating students, decreasing science-related anxiety, and stimulating their engagement in classroom work. The research has concluded that emotional intelligence of teachers is crucial in enhancing academic performance of students regarding science at the secondary level.